2017
DOI: 10.2196/mhealth.7871
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of User Engagement With the Mobile App, Manage My Pain: Results of a Data Mining Investigation

Abstract: BackgroundPain is one of the most prevalent health-related concerns and is among the top 3 most common reasons for seeking medical help. Scientific publications of data collected from pain tracking and monitoring apps are important to help consumers and healthcare professionals select the right app for their use.ObjectiveThe main objectives of this paper were to (1) discover user engagement patterns of the pain management app, Manage My Pain, using data mining methods; and (2) identify the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 30 publications
(47 reference statements)
2
45
0
Order By: Relevance
“…Thus, for a subset of people with headache, adherence to the electronic headache diary was high. The rates of electronic headache diary adherence observed among all the participants in this study were similar to those described in both clinical research and commercial chronic pain self‐monitoring apps. The rates of electronic headache diary adherence observed among participants who were “completers” were higher, and more consistent with the rest of the headache literature, which predominantly includes data from clinical trials.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, for a subset of people with headache, adherence to the electronic headache diary was high. The rates of electronic headache diary adherence observed among all the participants in this study were similar to those described in both clinical research and commercial chronic pain self‐monitoring apps. The rates of electronic headache diary adherence observed among participants who were “completers” were higher, and more consistent with the rest of the headache literature, which predominantly includes data from clinical trials.…”
Section: Discussionsupporting
confidence: 79%
“…Interim analysis of an ongoing randomized clinical trial evaluating a behavioral migraine treatment found similar average adherence to electronic headache diaries as identified in previous trials (13% for 2 months of monitoring, 20% for 4 months of monitoring), but also found that a small number of participants (7 out of 38) accounted for a disproportionate amount of missing days . In the chronic pain literature, higher complexity of pain problems and taking more medication were associated with higher rates of adherence to a self‐monitoring app; however, little is known about the characteristics of people with headache that may be associated with adherence to electronic headache diaries. Understanding factors associated with adherence to electronic headache diaries can help identify subgroups of patients less likely to adhere, and aid in intervention development to improve adherence, to electronic headache diaries.…”
Section: Introductionmentioning
confidence: 99%
“…movement through pages) requires alternative methods to identify and inform subsequent statistical analysis. Therefore, techniques such as visualisation and process mining may be more informative as they can reveal patterns of usage within the data, such as workflow through an intervention, clustering by participant groups, and temporal details [10,[21][22][23][24]. In applying stage 3 of the framework, the required data format for any analytical software should be considered.…”
Section: Stage 3: Preparation For Analysismentioning
confidence: 99%
“…It is noteworthy that there are several mobile apps proving the applicability of smart mobile devices in the context of data collection scenarios, such as Manage My Pain [11] or Track Your Tinnitus [12]. Although the participants involved in respective scenarios gave positive feedback, several shortcomings could still be observed.…”
Section: Introductionmentioning
confidence: 99%